Assessing the sustainability reporting quality of oil & gas companies in Indonesia and Malaysia: examining the influence of board and CEO chair characteristics - Dian Imanina Burhany; Moch. Edman Syarief; Iwan Setiawan; Muhamad Umar Ma; Nafisah Ruhana; Mohd Raziff Jamaluddin; Hanudin Amin (EDP Sciences, 2024)
Presently, companies, particularly those significantly impacting the environment and society, are obliged to report their sustainability-related actions. This research focuses on exploring how the characteristics of the board and the chief executive officer contribute to enhancing the quality of sustainability reporting in Oil & Gas companies operating in Indonesia and Malaysia. The study involves an analysis of 18 companies across the years 2012-2022, forming an unbalanced panel dataset encompassing a total of 178 company-year observations. Utilizing the random effect model, the findings suggest that the board's size, an independent board, and a CEO with a lengthier tenure significantly contribute to improving the quality of corporate sustainability reporting. On the other hand, the gender diversity of the board and the age of the CEO do not exhibit a significant impact on enhancing the quality of corporate sustainability reporting. This research fills a gap in the existing literature by investigating the correlation between board and CEO characteristics and the quality of sustainability reporting within the Oil & Gas sector, specifically focusing on the Indonesian and Malaysian contexts. Moreover, it offers valuable insights and understanding for industry practitioners.